Efektivitas Siber Konseling Untuk Meningkatkan Layanan Konseling Pendidikan: Analisis Isi dari tahun 2019-2024 - Muhammad, Rifqi (Inovasi: Jurnal Diklat Keagamaan, 2024)
Background by the absence of meta data documenting evidence of the effectiveness of cyber counseling in the context of educational counseling services for students. The objectives of the study: 1) to review the literature on technology used in cyber counseling in educational counseling services; 2) to review the effectiveness of cyber counseling to improve educational counseling services. This study uses content analysis on n = 20 literatures. This study uses a comprehensive review of n = 20 literatures. Literature search on the main database, namely SOPUS with the help of the PoP application, spanning the years 2019-2024. Data collection from June 2024 to July 2024. Results of the study: 1) The technology used in cyber counseling in educational counseling services includes: Skype, Silver Cloud, email, SMS, online sync video technology, website, IZ Hero Challenge, iCBT, Whatsapp, and computer-internet. Cyber counseling utilizes technology to facilitate individual counseling services, career counseling, psychological counseling, and social counseling. 2) Evidence of the effectiveness of cyber counseling that uses technology assistance to improve educational counseling services is seen from the results of counseling increasing (n = 16) and decreasing (n = 4). Proven to increase resilience, subjective risk intelligence, career adaptability, self-efficacy, optimism, and life satisfaction; understanding of social support in online peer groups for career counseling; students' humility; career decision-making skills; mental health; positive affect; subjective well-being; and future perspectives; access information; and assist students in getting counseling. Proven to reduce mental stress, anxiety, depression, obsessive-compulsive disorder, interpersonal sensitivity, and anxiety. These investigations include investigations in Indonesia, the United States, Turkey, Singapore, Iran, Ghana, Malaysia, Germany, Europe, and Italy.